Experiences of Grade 10 teachers and learners in learning Sepedi Home Language poetry aspects at Magatle Circuit, Capricorn South, Limpopo Province, South Africa - Maphalla, Fortune (My University, 2024)
This study aimed to investigate difficulties experienced during the teaching and learning of poetry in the Grade 10 Sepedi Home Language classroom at Magatle Circuit, Capricorn South, Limpopo Province, South Africa. Amongst other prescribed literary genres like plays, novels, folktales, and short stories, poetry is one genre that is deemed worthy of art rather than mere amusement. One of the key roles of educators is to integrate poetry skills from cultural practices with formal education, using relevant and effective teaching strategies. The study employed a qualitative case study design. Data were collected through non-participant observation, and semi-structured interviews and were analysed thematically by coding them into sections and subsections according to the themes that emerged. The findings of the study revealed that learners and teachers have negative attitudes towards the poetic nature of the language used in poetry. The study, therefore, recommends that teachers be upskilled with strategies to teach poetry and that learners should be motivated to appreciate poetry as one of the important genres taught in schools
Thesis (M.Ed. ( Language Education)) -- University of Limpopo, 2024
Keywords: Poetry; Poetic language; Poetry analysis; Sepedi Home Language; Northern Sotho language -- South Africa -- Limpopo; Poetry -- Study and teaching (Secondary); Northern Sotho language -- Study and teaching